Environmentally friendly stainless steel passivation solution and preparation method and application thereof
By combining nano-silica and sepiolite powder with epoxy resin, a dense film layer is formed, which solves the toxicity problem of hexavalent chromium passivation liquid, and achieves efficient passivation of environmentally friendly stainless steel, which significantly improves the metal material Corrosion resistance.
Patent Information
- Application Number
- CN202411568462.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The hexavalent chromium used in existing stainless steel passivation fluids is considered to be highly toxic carcinogens, which has restricted its application after increasing environmental awareness and requires finding safer alternatives.
Nanosilica and sepiolite powder are modified and combined with epoxy resin to form a dense passivation film. The corrosion resistance of the film layer is enhanced through the chemical action of materials such as carboxymethyl chitosan and acrylamide. , alternative to the traditional hexavalent chromium passivation scheme.
The preparation of environmentally friendly stainless steel passivation liquid is realized, which significantly improves the corrosion resistance of metal materials, avoids the toxicity risk of hexavalent chromium, and avoids the problem of corrosion resistance reduction caused by uneven dispersion of raw materials.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, and in particular to an environmentally friendly stainless steel passivation solution and a preparation method and application thereof. Background Art
[0002] Stainless steel is widely used in many industries due to its excellent corrosion resistance, high temperature resistance, low temperature resistance, wear resistance and beautiful appearance, and has become an indispensable material in modern industry and life. It is not only used in high-tech fields such as aerospace, atomic energy, marine development and petrochemical industry, but also plays an important role in daily life such as automobile manufacturing, building decoration, household appliances, kitchen utensils, etc. With the continuous advancement of technology and the improvement of people's requirements for material performance, the application field of stainless steel is also expanding.
[0003] Although stainless steel has good performance, surface defects and corrosion hazards are still problems that cannot be ignored during processing. These defects may include black oxide scale, yellow welds, grease residue during cold drawing, etc., which will affect the appearance and corrosion resistance of stainless steel. Therefore, in order to improve the appearance quality and corrosion resistance of stainless steel, stainless steel after processing usually needs to be passivated.
[0004] The principle of passivation treatment is to remove pollutants and defects on the surface of stainless steel through chemical reaction, forming a passivation film with chromium as the main component. This passivation film has high density and stability, which can effectively prevent stainless steel from reacting with other substances in the external environment, thereby achieving the purpose of passivation.
[0005] Hexavalent chromium passivation is a traditionally widely used technology. This solution can form a dense passivation film on the surface of stainless steel, greatly improving its corrosion resistance. A significant advantage of the hexavalent chromium passivation film is its self-repairing ability. Even if the surface is scratched, the hexavalent chromium in the film layer can still repair the passivation film, thereby maintaining good corrosion resistance. However, hexavalent chromium is considered a highly toxic carcinogen. With the improvement of environmental awareness, more and more countries and regions have gradually banned the use of hexavalent chromium, requiring companies to seek safer alternatives.
[0006] Chinese patent document CN102168265B discloses a chromium-free composite passivator and a preparation method thereof. The contents of the components are as follows by mass percentage: 3.0-10% of γ-methacryloyloxytrimethoxysilane, 0.1-3.0% of sodium molybdate, 0.1-5.0% of cerium chloride, 0.5-4.0% of phosphoric acid, 0.5-4.0% of acetic acid, 15-20% of water-soluble epoxy resin, 5-15% of water-soluble acrylic resin, 10-30% of water, and 20-40% of ethanol. A large amount of ethanol is used in the above scheme, which greatly limits the promotion and application of the product. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide an environmentally friendly stainless steel passivation solution and a preparation method and application thereof.
[0008] In order to achieve the above object, the present invention adopts the following technical scheme:
[0009] A method for preparing an environmentally friendly stainless steel passivation solution comprises the following steps:
[0010] S1, dispersing nano-silica in an ethanol aqueous solution, then adding an epoxy silane coupling agent, stirring for 2-4 hours, then adding a carboxymethyl chitosan solution, reacting at a constant temperature, and after the reaction is completed, filtering, washing, and drying to obtain modified nano-silica;
[0011] S2, dispersing the sepiolite powder in an ethanol aqueous solution, then adding a vinyl silane coupling agent, stirring for 2-4 hours, filtering, washing, and drying to obtain a pretreated sepiolite powder;
[0012] S3, dispersing the pretreated sepiolite powder in deionized water, then adding acrylamide, allyloxy polyoxyethylene ether and initiator, heating and stirring to react, after the reaction is completed, filtering, washing and drying to obtain modified sepiolite powder;
[0013] S4. Add modified nano-silicon dioxide and modified sepiolite powder into epoxy resin and stir evenly to obtain stainless steel passivation liquid.
[0014] Preferably, in step S1, the mass ratio of nano-silica, epoxy silane coupling agent and carboxymethyl chitosan solution is 10-20:1-3:60-80, and the mass fraction of carboxymethyl chitosan solution is 3-6%.
[0015] Preferably, in step S1, the temperature of the isothermal reaction is 70-80° C., and the time of the isothermal reaction is 2-3 h.
[0016] Preferably, in step S2, the mass ratio of sepiolite powder to vinyl silane coupling agent is 10-15:1-3.
[0017] Preferably, in step S3, the mass ratio of pretreated sepiolite powder, acrylamide, allyloxy polyoxyethylene ether and initiator is 8-12:3-6:2-4:0.5-1.
[0018] Preferably, in step S3, the initiator is selected from persulfate.
[0019] Preferably, in step S3, the temperature of the heating and stirring reaction is 60-80° C., and the time of the heating and stirring reaction is 2-5 h.
[0020] Preferably, in step S4, the mass ratio of modified nano-silicon dioxide, modified sepiolite powder and epoxy resin is 4-8:2-3:100.
[0021] The invention provides a stainless steel passivation solution prepared by the preparation method.
[0022] The invention also provides application of the stainless steel passivation liquid in metal surface corrosion protection.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention first uses an epoxy silane coupling agent to treat nano-silica, introduces epoxy groups on the surface of the nano-silica, and then grafts carboxymethyl chitosan on the surface of the nano-silica through the cross-linking effect of the epoxy groups. The carboxymethyl chitosan has good film-forming properties and forms a film layer on the surface of the metal material. At the same time, the hydroxyl and amino groups in the carboxymethyl chitosan can react chemically with the epoxy groups in the epoxy resin to make the film layer denser, thereby preventing the corrosive medium from passing through the film layer, thereby improving the corrosion resistance of the metal material.
[0025] (2) The present invention forms a polymer grafted on the surface of sepiolite powder by an addition reaction between double bonds, so that the sepiolite powder can be better dispersed in the epoxy resin. At the same time, the polymer contains amide groups, which can form chemical bonds with the hydroxyl and amino groups in carboxymethyl chitosan and the epoxy groups in the epoxy resin, further enhancing the physical shielding effect, slowing down the contact between corrosive substances and the metal substrate, and protecting the metal substrate. At the same time, allyloxy polyoxyethylene ether has good dispersibility, which can effectively prevent the sepiolite powder from agglomerating, thereby avoiding the problem of reduced corrosion resistance of the metal substrate due to uneven dispersion of raw materials.
[0026] (3) The sepiolite powder provided by the present invention has a layered structure, and the polymer formed by acrylamide and allyloxy polyoxyethylene ether has a three-dimensional network structure. The modified nano-silicon dioxide is filled in the network structure, which greatly prolongs the diffusion path of corrosive substances, slows down the diffusion of corrosive substances, and further improves the anti-corrosion performance of the metal substrate. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0028] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0029] A method for preparing an environmentally friendly stainless steel passivation solution comprises the following steps:
[0030] S1. Preparation of modified nano-silica
[0031] The nano-silica is dispersed in an ethanol aqueous solution, and then an epoxy silane coupling agent is added, stirred for 2-4 hours, and then a carboxymethyl chitosan solution is added, and the reaction is carried out at a constant temperature. After the reaction is completed, the modified nano-silica is obtained by filtering, washing, and drying.
[0032] In this step, the mass ratio of nano-silica, epoxy silane coupling agent and carboxymethyl chitosan solution is 10-20:1-3:60-80.
[0033] In the present invention, the epoxy silane coupling agent is selected from KH560.
[0034] The mass fraction of the carboxymethyl chitosan solution is 3-6%, for example, 3%, 4%, 5%, or 6%.
[0035] In this step, the temperature of the isothermal reaction is 70-80°C, for example, 70°C, 72°C, 74°C, 75°C, 76°C, 78°C, and 80°C can be selected; the time of the isothermal reaction is 2-3h, for example, 2h, 2.5h, and 3h can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] In this step, the nano-silica is first treated with an epoxy silane coupling agent to introduce epoxy groups on the surface of the nano-silica, and then carboxymethyl chitosan is grafted on the surface of the nano-silica through the cross-linking effect of the epoxy groups. The carboxymethyl chitosan has good film-forming properties and forms a film layer on the surface of the metal material. At the same time, the hydroxyl and amino groups in the carboxymethyl chitosan can react chemically with the epoxy groups in the epoxy resin to make the film layer denser, thereby preventing the corrosive medium from passing through the film layer, thereby improving the corrosion resistance of the metal material.
[0037] S2. Preparation of pretreated sepiolite powder
[0038] The sepiolite powder is dispersed in an ethanol aqueous solution, and then a vinyl silane coupling agent is added, and the mixture is stirred for 2-4 hours. The mixture is filtered, washed, and dried to obtain the pretreated sepiolite powder.
[0039] In this step, the mass ratio of sepiolite powder to vinyl silane coupling agent is 10-15:1-3, for example, 10:1, 10:2, 10:3, 12:1, 12:2, 12:3, 15:1, 15:2, 15:3 can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] Wherein, the vinyl silane coupling agent is selected from vinyl trimethoxy silane, vinyl triethoxy silane or vinyl tri (β-methoxyethoxy) silane.
[0041] In this step, the sepiolite powder is treated with a vinyl silane coupling agent to introduce carbon-carbon double bonds on the surface of the sepiolite powder, which is beneficial to the subsequent reaction.
[0042] S3, dispersing the pretreated sepiolite powder in deionized water, then adding acrylamide, allyloxy polyoxyethylene ether and initiator, heating and stirring to react, after the reaction is completed, filtering, washing and drying to obtain modified sepiolite powder.
[0043] In this step, the mass ratio of the pretreated sepiolite powder, acrylamide, allyloxy polyoxyethylene ether and initiator is 8-12:3-6:2-4:0.5-1.
[0044] Wherein, the initiator is selected from persulfate, for example, ammonium persulfate, potassium persulfate or sodium persulfate.
[0045] The temperature of the heating and stirring reaction is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C can be selected; the time of the heating and stirring reaction is 2-5h, for example, 2h, 3h, 4h, 5h can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0046] In this step, acrylamide and allyloxy polyoxyethylene ether form a polymer grafted on the surface of the sepiolite powder through an addition reaction between double bonds, so that the sepiolite powder can be better dispersed in the epoxy resin. At the same time, the polymer contains amide groups, which can form chemical bonds with hydroxyl groups and amino groups in carboxymethyl chitosan and epoxy groups in the epoxy resin, further enhancing the physical shielding effect, slowing down the contact between corrosive substances and the metal substrate, and protecting the metal substrate. At the same time, allyloxy polyoxyethylene ether has good dispersibility, which can effectively prevent the sepiolite powder from agglomerating, and avoid the problem of reduced corrosion resistance of the metal substrate due to uneven dispersion of raw materials.
[0047] S4. Preparation of stainless steel passivation solution
[0048] The modified nano silicon dioxide and modified sepiolite powder are added into the epoxy resin and stirred evenly to obtain the stainless steel passivation liquid.
[0049] In this step, the mass ratio of modified nano-silicon dioxide, modified sepiolite powder and epoxy resin is 4-8:2-3:100, for example, 4:2:100, 4:3:100, 5:2:100, 5:3:100, 6:3:100, 8:2:100, 8:3:100 can be selected; but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] The present invention is further described below by means of specific examples, wherein the particle size of nano silicon dioxide is 60-80 nm; the mesh number of sepiolite powder is 4000 mesh; the brand of epoxy resin is E-44, CAS number: 61788-97-4.
[0051] Example 1
[0052] A method for preparing an environmentally friendly stainless steel passivation solution comprises the following steps:
[0053] S1. Disperse 10 g of nano-silica in 150 mL of 80 wt% ethanol aqueous solution, then add 1 g of silane coupling agent KH560, stir for 3 h, then add 60 g of 6 wt% carboxymethyl chitosan solution, and react at 70 ° C for 3 h. After the reaction is completed, filter, wash and dry to obtain modified nano-silica;
[0054] S2, dispersing 10g of sepiolite powder in 150mL, 80wt% ethanol aqueous solution, then adding 1g of vinyltrimethoxysilane, stirring for 3h, filtering, washing and drying to obtain pretreated sepiolite powder;
[0055] S3, dispersing 8g of pretreated sepiolite powder in 150mL of deionized water, then adding 3g of acrylamide, 2g of allyloxy polyoxyethylene ether and 0.5g of initiator ammonium persulfate, heating and stirring at 60°C for 5h, after the reaction is completed, filtering, washing and drying to obtain modified sepiolite powder;
[0056] S4. Add 4 g of modified nano-silicon dioxide and 2 g of modified sepiolite powder into 100 g of epoxy resin and stir evenly to obtain a stainless steel passivation solution.
[0057] Example 2
[0058] A method for preparing an environmentally friendly stainless steel passivation solution comprises the following steps:
[0059] S1, 20g of nano-silica was dispersed in 150mL of 80wt% ethanol aqueous solution, and then 3g of silane coupling agent KH560 was added, and stirred for 3h, followed by adding 80g of 6wt% carboxymethyl chitosan solution, and reacted at 80°C for 2h. After the reaction was completed, the modified nano-silica was obtained by filtering, washing and drying;
[0060] S2, dispersing 15g of sepiolite powder in 150mL, 80wt% ethanol aqueous solution, then adding 3g of vinyltriethoxysilane, stirring for 4h, filtering, washing and drying to obtain pretreated sepiolite powder;
[0061] S3, dispersing 12g of pretreated sepiolite powder in 150mL of deionized water, then adding 6g of acrylamide, 4g of allyloxy polyoxyethylene ether and 1g of initiator ammonium persulfate, heating and stirring at 80°C for 2h, after the reaction is completed, filtering, washing and drying to obtain modified sepiolite powder;
[0062] S4. Add 8 g of modified nano-silicon dioxide and 3 g of modified sepiolite powder into 100 g of epoxy resin and stir evenly to obtain a stainless steel passivation solution.
[0063] Example 3
[0064] A method for preparing an environmentally friendly stainless steel passivation solution comprises the following steps:
[0065] S1. Disperse 12 g of nano-silica in 150 mL of 80 wt% ethanol aqueous solution, then add 2 g of silane coupling agent KH560, stir for 3 h, then add 80 g of 3 wt% carboxymethyl chitosan solution, and react at 75 ° C for 2.5 h. After the reaction is completed, filter, wash and dry to obtain modified nano-silica;
[0066] S2, dispersing 12g of sepiolite powder in 150mL, 80wt% ethanol aqueous solution, then adding 2g of vinyltriethoxysilane, stirring for 4h, filtering, washing and drying to obtain pretreated sepiolite powder;
[0067] S3, dispersing 10g of pretreated sepiolite powder in 150mL of deionized water, then adding 5g of acrylamide, 3g of allyloxy polyoxyethylene ether and 0.8g of initiator ammonium persulfate, heating and stirring at 70°C for 4h, after the reaction is completed, filtering, washing and drying to obtain modified sepiolite powder;
[0068] S4. Add 6 g of modified nano-silicon dioxide and 2 g of modified sepiolite powder into 100 g of epoxy resin and stir evenly to obtain a stainless steel passivation solution.
[0069] Example 4
[0070] A method for preparing an environmentally friendly stainless steel passivation solution comprises the following steps:
[0071] S1. Disperse 15 g of nano-silica in 150 mL of 80 wt% ethanol aqueous solution, then add 2.5 g of silane coupling agent KH560, stir for 3 h, then add 80 g of 5 wt% carboxymethyl chitosan solution, and react at 80 ° C for 2 h. After the reaction is completed, filter, wash and dry to obtain modified nano-silica;
[0072] S2, dispersing 12g of sepiolite powder in 150mL, 80wt% ethanol aqueous solution, then adding 2.5g of vinyltrimethoxysilane, stirring for 2h, filtering, washing and drying to obtain pretreated sepiolite powder;
[0073] S3, dispersing 9g of pretreated sepiolite powder in 150mL of deionized water, then adding 4g of acrylamide, 4g of allyloxy polyoxyethylene ether and 1g of initiator ammonium persulfate, heating and stirring at 80°C for 2h, after the reaction is completed, filtering, washing and drying to obtain modified sepiolite powder;
[0074] S4. Add 5 g of modified nano-silicon dioxide and 2.5 g of modified sepiolite powder into 100 g of epoxy resin and stir evenly to obtain a stainless steel passivation solution.
[0075] Comparative Example 1
[0076] A method for preparing an environmentally friendly stainless steel passivation solution comprises the following steps:
[0077] S1. Disperse 10 g of nano-silica in 150 mL of 80 wt% ethanol aqueous solution, then add 1 g of silane coupling agent KH560, stir for 3 h, filter, wash and dry to obtain modified nano-silica;
[0078] S2, dispersing 10g of sepiolite powder in 150mL, 80wt% ethanol aqueous solution, then adding 1g of vinyltrimethoxysilane, stirring for 3h, filtering, washing and drying to obtain pretreated sepiolite powder;
[0079] S3, dispersing 8g of pretreated sepiolite powder in 150mL of deionized water, then adding 3g of acrylamide, 2g of allyloxy polyoxyethylene ether and 0.5g of initiator ammonium persulfate, heating and stirring at 60°C for 5h, after the reaction is completed, filtering, washing and drying to obtain modified sepiolite powder;
[0080] S4. Add 4 g of modified nano-silicon dioxide and 2 g of modified sepiolite powder into 100 g of epoxy resin and stir evenly to obtain a stainless steel passivation solution.
[0081] Compared with Example 1, Comparative Example 1 does not use carboxymethyl chitosan to modify the nano-silicon dioxide.
[0082] Comparative Example 2
[0083] A method for preparing an environmentally friendly stainless steel passivation solution comprises the following steps:
[0084] S1. Disperse 10 g of nano-silica in 150 mL of 80 wt% ethanol aqueous solution, then add 1 g of silane coupling agent KH560, stir for 3 h, then add 60 g of 6 wt% carboxymethyl chitosan solution, and react at 70 ° C for 3 h. After the reaction is completed, filter, wash and dry to obtain modified nano-silica;
[0085] S2. Add 4 g of modified nano-silicon dioxide and 2 g of sepiolite powder into 100 g of epoxy resin and stir evenly to obtain a stainless steel passivation solution.
[0086] Compared with Example 1, in Comparative Example 2, the sepiolite powder was not modified.
[0087] Comparative Example 3
[0088] A method for preparing an environmentally friendly stainless steel passivation solution comprises the following steps:
[0089] S1. Disperse 10 g of nano-silica in 150 mL of 80 wt% ethanol aqueous solution, then add 1 g of silane coupling agent KH560, stir for 3 h, then add 60 g of 6 wt% carboxymethyl chitosan solution, and react at 70 ° C for 3 h. After the reaction is completed, filter, wash and dry to obtain modified nano-silica;
[0090] S2, dispersing 10g of sepiolite powder in 150mL, 80wt% ethanol aqueous solution, then adding 1g of vinyltrimethoxysilane, stirring for 3h, filtering, washing and drying to obtain pretreated sepiolite powder;
[0091] S3, dispersing 8g of pretreated sepiolite powder in 150mL of deionized water, then adding 3g of acrylamide and 0.5g of initiator ammonium persulfate, heating and stirring at 60°C for 5h, after the reaction is completed, filtering, washing and drying to obtain modified sepiolite powder;
[0092] S4. Add 4 g of modified nano-silicon dioxide and 2 g of modified sepiolite powder into 100 g of epoxy resin and stir evenly to obtain a stainless steel passivation solution.
[0093] Compared with Example 1, in Comparative Example 3, no allyloxy polyoxyethylene ether was added during the modification process of sepiolite powder.
[0094] The 304 stainless steel was immersed in the passivation solution of Examples 1-4 and Comparative Examples 1-3 respectively, taken out after 5 minutes, and dried at 60° C., that is, a passivation film was plated on the surface of the steel.
[0095] The stainless steel materials with the passivation film on the surface obtained in Examples 1-4 and Comparative Examples 1-3 were subjected to a neutral salt spray test and a salt water resistance test.
[0096] Neutral salt spray test: The test method refers to GB / T 10125-2012. The corrosion resistance of the sample is evaluated by observing the time when white rust appears. The test is repeated three times in parallel and the results are averaged.
[0097] Salt water resistance test: The steel samples with the passivation film on the surface were immersed in a sodium chloride solution with a mass concentration of 3.5%. The corrosion resistance of the samples was evaluated by observing the time when white rust appeared. The test was repeated three times in parallel and the results were averaged.
[0098] The test results are shown in the following table:
[0099] Neutral salt spray test white rust appearance time (h) Salt water resistance test white rust appearance time (h) Example 1 223 137 Example 2 249 153 Example 3 238 144 Example 4 231 146 Comparative Example 1 197 104 Comparative Example 2 162 88 Comparative Example 3 205 112
[0100] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.
Claims
1. A method for preparing an environmentally friendly stainless steel passivation solution, characterized in that: The steps include: S1, dispersing nano-silica in an ethanol aqueous solution, then adding an epoxy silane coupling agent, stirring for 2-4 hours, then adding a carboxymethyl chitosan solution, reacting at a constant temperature, and after the reaction is completed, filtering, washing, and drying to obtain modified nano-silica; S2, dispersing the sepiolite powder in an ethanol aqueous solution, then adding a vinyl silane coupling agent, stirring for 2-4 hours, filtering, washing, and drying to obtain a pretreated sepiolite powder; S3, dispersing the pretreated sepiolite powder in deionized water, then adding acrylamide, allyloxy polyoxyethylene ether and initiator, heating and stirring to react, after the reaction is completed, filtering, washing and drying to obtain modified sepiolite powder; S4. Add modified nano-silicon dioxide and modified sepiolite powder into epoxy resin and stir evenly to obtain stainless steel passivation liquid.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of nano-silica, epoxy silane coupling agent and carboxymethyl chitosan solution is 10-20:1-3:60-80, and the mass fraction of carboxymethyl chitosan solution is 3-6%.
3. The preparation method according to claim 1, characterized in that: In step S1, the temperature of the isothermal reaction is 70-80° C., and the time of the isothermal reaction is 2-3 hours.
4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of sepiolite powder to vinyl silane coupling agent is 10-15:1-3.
5. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the pretreated sepiolite powder, acrylamide, allyloxy polyoxyethylene ether and initiator is 8-12:3-6:2-4:0.5-1.
6. The preparation method according to claim 1, characterized in that: In step S3, the initiator is selected from persulfate.
7. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the heating and stirring reaction is 60-80° C., and the time of the heating and stirring reaction is 2-5 h.
8. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of modified nano-silicon dioxide, modified sepiolite powder and epoxy resin is 4-8:2-3:
100.
9. The stainless steel passivation solution prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the stainless steel passivation solution as claimed in claim 9 in metal surface corrosion protection.
Citation Information
Patent Citations
Chromium-free composite passivator and preparation method thereof
CN102168265B
Epoxy resin antirust paint and preparation method thereof
CN103073969A
Surface treatment method and base material
JP2005320595A
Cited By
Water-based environment-friendly stainless steel surface treatment passivator and preparation method thereof
CN120776291A